Material and Process Modification to Improve Manufacturability of Low-Lead Copper Alloys by Low-Pressure Die Casting Method - Ali Serdar Vanli; Muhammed Hakan Karas (Metals, 2025)
Copper alloys are widely used in faucet production due to their formability, enabling the casting of complex shapes, as well as to their antibacterial properties and good corrosion resistance. This study examined a faucet produced by the low-pressure die casting method, focusing on alternatives to lead (Pb) in copper alloys. Fluidity, casting rejection rates, and mechanical and microstructural properties were assessed. Additionally, lead-free and environmentally friendly brass alloy developments in the literature were reviewed. The experimental work involved producing a faucet from aluminum, antimony, and a bismuth-modified low-lead alloy using low-pressure casting. As faucet material, the antimony-supplemented alloy exhibited superior strength and optimal hardness. It also demonstrated better microstructural distribution and the highest production efficiency (at 81%). These findings highlight the significant advantages of the addition of antimony over aluminum and bismuth in faucet casting. The results are promising for both the casting process and subsequent mechanical operations, suggesting that antimony could enhance production quality and efficiency in low-pressure die-cast copper alloys.